Catabolism of Space and utilization of community as A Survival Strategy of Pesantren - Heryawan Asnawi, Yudha; Soetarto, Endriatmo (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTThrough out in history of pesantren is not a stagnant entity. Pesantren has undergone various linkages from early history to this present. Initially pesantren is an institution with simple spaces which are turned into an institution with the complexity of space. Consider from the physical structure, initially, pesantren has three buildingsor facilities that are the mosque, majlis-taklim and house of Kyai. The third building is a building for education space. Along with the development in the peripheral of pesantren environment currently emerging business space.This paper discusses the development of pesantren space, using the conditions of pesantren in the late 19th century to the present. The discussion using an arrangement of the history and growth of pesantren space by taking the case at Sidogiri Pesantren, Pasuruan, East Java.This paper uses a constructivist approach that is hermeneutic and dialectical where the individual social construction can acquire and known through interactions between researcher and actors of research. In addition, this study also emphasizes empathy and dialectic interaction between researchers and informants in order to reconstruct the social reality under study with qualitative methods. The survey results of the research revealed that the emerging new spaces at the pesantren that is the internal business space and external business collaboration space that complements the mosque, majlis taklim and house of Kyai who had been already there. The new of economy spaces (business spaces), and with the community formed can be a tool for survival strategy of Pesantren. Even to this day pesantren persist with the principles of Islamic, but remains on the threat of consequences: without the moral control of religion, and the charisma of kyai, Pesantren can be a greedy capitalist machine as generally.Keywords: transformation, economic space, pesantrenABSTRAKSepanjang sejarahnya pesantren bukanlah entitas stagnan. Pesantren telah mengalami berbagai kebersinggungan dari awal sejarahnya hingga saat ini. Pesantren yang pada awalnya adalah sebuah lembaga dengan ruang-ruang yang sederhana kini berubah menjadi lembaga dengan kompleksitas ruang. Dilihat dari struktur fisik, pada awalnya pesantren mempunyai tiga bangunan atau fasilitas yaitu masjid, majlis taklim dan rumah Kyai. Ketiga bangunan tersebut merupakan bangunan untuk ruang pendidikan. Seiring dengan perkembangan, saat ini di lingkungan pesantren muncul ruang-ruang bisnis. Tulisan ini membahas mengenai perkembangan ruang pesantren, menggunakan kondisi pesantren pada akhir abad 19 hingga saat ini. Pembahasan menggunakan Setting sejarah dan pertumbuhan ruang pesantren dengan mengambil contoh kasus di Pondok Pesantren Sidogiri, Pasuruan Jawa Timur. Tulisan ini menggunakan pendekatan konstruktivis yang bersifat hermeunetikal dan dialektikal dimana konstruksi sosial individu dapat diperoleh dan diketahui melalui interaksi antara peneliti dan tineliti. Di samping itu, penelitian ini juga menekankan empati dan interaksi dialektif antara peneliti dan informan dalam rangka merekonstruksi realitas sosial yang diteliti dengan metode kualitatif. Dari hasil penelitian diketahui bahwa muncul ruang-ruang baru di pesantren yaitu ruang usaha internal dan ruang kolaborasi bisnis eksternal yang melengkapi ruang masjid, majlis taklim dan rumah kyai yg selama ini sudah ada.Ruang-ruang ekonomi baru (ruang bisnis) dan pembentukan komunitas telah menjadi sebuah alat dan strategi kebertahanan pesantren. Sekalipun sampai saat ini pesantren bertahan dengan prinsip keislaman, namun tetap pada ancaman konsekuensi: ketika terjadi pelemahan pada kontrol moral dari pengajaran agama, dan kharisma kyai yang dimilikinya, maka pesantren dapat menjadi mesin kapitalisme yang serakah sebagaimana umumnya.Kata kunci: transformasi, ruang ekonomi pesantren